Spectophotometric Study of Interaction between Sodium Carrageenate and Cationic Dyes - R. Nandini; B. Vishalakshi (E-Journal of Chemistry)
The interaction of two cationic dyes, namely, methylene (MB) and acridine orange (AO) with an anionic polyelectrolyte, namely, sodium carrageenate (NaCar) has been investigated by spectrophotometric method and spectrofluorimetric method. The polymer induced metachromasy in the dyes resulting in the shift of the absorption maxima of the dyes towards shorter wavelengths.The stability of the complexes formed between acridine orange and sodium carrageenate was found to be lesser than that formed between methylene blue and sodium carrageenate. This fact was further confirmed by reversal studies using alcohols, urea, surfactants and electrolytes. The interaction parameters revealed that binding between acridine orange and sodium carrageenate was mainly due to electrostatic interaction while that between methylene blue and carrageenate is found to involve both electrostatic and hydrophobic forces. The effect of the structure of the dye and its relation to metachromasy has been discussed.